Effect of Zonal Hydraulics on Energy Consumption and Boom Structure of a Micro-Excavator - Abinab Niraula; Shuzhong Zhang; Tatiana Minav; Matti Pietola (Energies, 2018)
This paper investigates the effect of extra weight caused by the Direct Driven Hydraulics (DDH) in a micro-excavator. These projects are investigating the implementation of zonal or decentralized hydraulics for non-road mobile machinery (NRMM) and stationary industrial applications. The benefit of DDH is the combination of electric and hydraulic technologies in a compact package compared to conventional hydraulics, which enables a reduction of potential leakage points, flexible tubing, and boosting of the system efficiency due to switching to direct pump control instead of a loss-generating conventional valve-based control. In order to demonstrate these benefits for the excavator case, this paper proposes a system model approach to assess and predict energy consumption of the zonal hydraulics approach implemented with DDH in various working cycles, complemented by a structural analysis. The finite element analysis utilized for this demonstrated that the extra weight and selected location of DDH units do not negatively affect the structure of the excavator. Simulation results demonstrated that the energy consumption is approximately 15% higher with extra weight added by the three DDH units. Although approximately 20% more regeneration energy is produced, taking into account the regeneration energy, the increases in energy consumption are about 12%.